The Good, the Bad and the Unthinkable of Learner Autonomy in EFL - Sevilla Morales, Henry (2020)
This study assesses the relation between self-evaluation and the development of learner autonomy (LA) in English as a foreign language (EFL). Using action-research, the investigation included 22 first-year students taking an oral communication and listening comprehension course in English at the Universidad Nacional, Costa Rica. Data collection instruments included weekly plan sheets, student diaries, and student portfolios and were subject to several validity measures. Broadly, findings suggest a connection between self-evaluation and the promotion of LA in EFL in four areas: time management, self-awareness and goal-setting, sense of achievement, and skills integration.